Broadband Q-Factor Imaging for Geofluid Detection in the Gulf of Trieste (Northern Adriatic Sea) - Vesnaver, Aldo; Böhm, Gualtiero; Busetti, Martina; Dal Cin, Michela; Zgur, Fabrizio (Frontiers in Earth Science, 2021)
Seismic surveys allow estimating lithological parameters, as P-wave velocity and anelastic absorption, which can detect the presence of fracture and fluids in the geological formations. Recently, a new method has been proposed for high-resolution imaging of anelastic absorption, which combines a macro-model from seismic tomography with a micro-model obtained by the pre-stack depth migration of a seismic attribute, i.e., the instantaneous frequency. As a result, we can get a broadband image that provides clues about the presence of saturating fluids. When the saturation changes sharply, as for gas reservoirs with an impermeable caprock, the acoustic impedance contrast produces “bright spots” because of the resulting high reflectivity at its top. When the fluid content changes smoothly, the anelastic absorption becomes a good detector, as fluid-filled formations absorb more seismic energy than hard rocks. We apply this method for imaging the anelastic absorption in a regional seismic survey acquired by OGS in the Gulf of Trieste (northern Adriatic Sea, Italy).